Is there a role for BLADE acquisition in T2-weighted breast MRI? - ÇİNKO, MURAT (TAYLOR & FRANCIS LTD, 2010)
Purpose: To compare T2W BLADE acquisition breast MR images with routine T2W images in the evaluation of motion artifacts and overall image quality. Material and Methods: MRI was performed with a 1.5 T system on 25 volunteers and 25 consecutive patients with identical imaging parameters for both MRI sequences (TR 5240 ms, TE 112-108 ms, acquisition 1, spatial resolution 0.9x0.9x 4 mm). Motion and flow artifacts and pectoral muscle and lesion contour delineations were assessed. Signal to noise ratios (SNRs) of images and contrast to noise ratios (CNRs) of the incidental lesions were calculated. The results were evaluated with the Wilcoxon signed-ranks test. Results: Of the 50 patients, 44 were included in the analysis (mean age 42.1 years). Motion artifacts were prominent in 48% cases on routine T2W and in only 2% of BLADE cases. The SNR values of BLADE images were significantly higher than routine T2W (P < 0.05). Pectoral muscle contours were better assessed on BLADE in all cases. Sequence performances were similar in flow artifacts, CNR values, and contour delineation of incidental lesions. The readers chose BLADE sequence MRI in 25 cases and found the overall performance of sequences equal in 19 cases. None of the readers preferred routine T2W to BLADE. Conclusion: The performance of BLADE is superior to routine T2W images in eliminating motion artifacts, provides better SNRs, shows detailed pectoral muscle contours, and may be the sequence of choice.
Keywords: PROPELLER MRI; MOTION CORRECTION; UPPER ABDOMEN; HEAD MOTION; BRAIN; QUALITY; LIVER; TESLA